2020
DOI: 10.3892/ol.2020.12215
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑155‑5p inhibits the invasion and migration of prostate cancer cells by targeting SPOCK1

Abstract: The aim of the present study was to determine the effect of microRNA (miR)-155-5p on the expression of testican-1 (SPOCK1) and the invasion and migration of prostate cancer cells in vitro . Bioinformatics analysis and molecular biology assays revealed that SPOCK1 may be a direct target gene of miR-155-5p. In addition, a negative correlation was identified between SPCOK1 and miR-155-5p expression in prostate tumor tissues and cell lines. miR-155-5p mimic transfection inhibited SPOCK1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…miR-155 exerts different biological functions in different cell types and disease models. In certain tumors, it acts as an oncogene to promote cell proliferation, invasion, and metastasis (55)(56)(57)(58), whereas, in other tumors, it acts as a tumor suppressor to inhibit cell proliferation and promote apoptosis (59,60). Li et al (61) reported that triptolide could significantly induce the expression of miR-155 both in normal human hepatocytes and in rodent liver tissues, and inhibition of miR-155 mitigated the hepatic damage caused by triptolide.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 exerts different biological functions in different cell types and disease models. In certain tumors, it acts as an oncogene to promote cell proliferation, invasion, and metastasis (55)(56)(57)(58), whereas, in other tumors, it acts as a tumor suppressor to inhibit cell proliferation and promote apoptosis (59,60). Li et al (61) reported that triptolide could significantly induce the expression of miR-155 both in normal human hepatocytes and in rodent liver tissues, and inhibition of miR-155 mitigated the hepatic damage caused by triptolide.…”
Section: Discussionmentioning
confidence: 99%
“…However, cell-free and EV-derived miRNAs do not necessarily show the same expression profiles in urine [ 65 ]. miR-155-5p has been found to inhibit the migration of prostate cancer cells [ 66 ] and a potential target for antitumoral treatments [ 67 ]. It has also been proposed that downregulation of miR-186-5p promotes cell proliferation and invasion due to its effect on Twist1 [ 68 ], and low levels of miR-186-5p have also been linked to other tumours such as colorectal and esophageal cancer [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-454 is highly expressed in PCa and targets the well-known tumor suppressor Nmyc downstream-regulated gene 2 (NDRG2) which consequently induces proliferation and invasion of PCa cells [74]. miR-454 was also shown to activate WNT/ß-catenin signaling which is able to interact with Ras so that miR-454 might contribute to bone metastasis in PCa via these pathways [99]. Its potential as therapeutic target is consistently suggested [100], but not well-validated in PCa yet.…”
Section: Mir-454mentioning
confidence: 99%